Analisis kemampuan pembuktian matematis parabola menggunakan guided learning berdasarkan tingkat resiliensi - Hidayati, Destia Wahyu; Wahyuni, Arie (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
One of the geometry materials at the high school level is a parabolic. The ability to prove parabolic formulas is needed by students majoring in Mathematics Education who will become mathematics teachers after graduating. Having an understanding of proof of the formula will make learning more meaningful. The purpose of this research is to find out a description of the proof of parabolic formula based on high, medium, and low resilience levels, so that various obstacles can be overcome early. This research is qualitative research. Data collection techniques used resilience questionnaires, test questions to prove the parabola formula, and interviews. The data analysis technique used data triangulation. The results showed that (1) there are three indicators in mathematical proof of parabolic mastered by students at high, medium, and low resilience levels, namely drawing the vertex, fixed point, and directrix line, determining the length of the two points, determining the results of the equation squared, (2) determining the coordinates of the vertex, fixed point, and the equations of the directrix mastered by students with a high level of resilience, but not yet mastered by students at moderate and low resilience levels, (3) determining two lines of the same length in the image according to the definition parabolic and determining the results of the multiplication distribution on addition and subtraction have been mastered by students at high and medium resilience levels, but not yet mastered by students at low resilience levels,